Decadal‐scale response of detritivorous surgeonfishes (family Acanthuridae) to no‐take marine reserve protection and changes in benthic habitat. Issue 5 (29th November 2018) - Russ, Garry R.; Payne, Cody S.; Bergseth, Brock J.; Rizzari, Justin R.; Abesamis, Rene A.; Alcala, Angel C.
Abstract : No‐take marine reserves (NTMR) are increasingly being implemented to mitigate the effects of fishing on coral reefs, yet determining the efficacy of NTMRs depends largely on partitioning the effects of fishing from the effect of benthic habitat. Species of coral‐reef fishes typically decline in density when subjected to fishing or benthic disturbances, but this is not always the case. This study documents the long‐term (8–31 years) response of six species of detritivorous surgeonfishes (family Acanthuridae) to NTMR protection and benthic habitat change at four islands (Apo, Sumilon, Mantigue, Selinog) in the central Philippines, each island with a NTMR and a monitored fished site. Despite being subject to moderate fishing pressure, these species did not increase in density with NTMR protection. However, density of these surgeonfishes had a strong negative relationship with cover of live hard coral and a strong positive relationship with cover of dead substratum (sand, rubble, hard dead substratum). These surgeonfishes typically feed over dead substrata and thus probably increase in density following large environmental disturbances that substantially reduce live hard coral cover. Here, we describe effects of environmental disturbance events ( e.g., use of explosives, typhoons) that reduced live hard‐coral cover and subsequent large increases (up to 25 fold) in surgeonfish densities, which then slowly (over 5–15 years) decreased in density as live hard coral recovered. Density of these functionally important surgeonfish species was influenced more by changes to benthic cover than by NTMR protection. Thus, we highlight the greater importance of bottom‐up controls ( i.e., benthic changes to food availability) than top‐down control ( i.e., fishing) on a functionally important group of coral‐reef fishes.